Analisis Pengaruh Kepemilikan Asing dalam Memoderasi Karakteristik CEO terhadap Kualitas Pelaporan Keuangan - Venessa, Jessy; Mardianto, Mardianto (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The purpose of this study is to determine the effect of CEO characteristics on the quality of financial statements with foreign ownership as moderation for non-financial companies listed on the IDX (Indonesia Stock Exchange) BEI from 2018 to 2022. The measurement of financial reporting quality in this study uses earnings management. However, the quality of financial statements is inversely proportional to earnings management so that the higher the earnings management value, the lower the quality of financial reporting in the company. This study has a population of 824 companies and after going through the sampling process obtained 378 companies or 1,890 data which became the research sample. The method applied in analyzing research data is using panel regression analysis and tested using Eviews. The results of the study indicate that CEO expertise, CEO gender, CEO age and CEO ownership have no significant effect on earnings management so that the hypothesis for these variables is not proven. The CEO tenure variable has a significant positive effect on earnings management and foreign ownership does not affect the relationship between CEO characteristics and earnings management.